RESPON PEMBERIAN PUPUK UREA DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN KANDUNGAN MINYAK ATSIRI TANAMAN JAHE MERAH [Zingiber officinale (L.) Rosc var. rubrum ] - Linda Saputri; Endah Dwi Hastuti; Rini Budi Hastuti (Jurnal Akademika Biologi, 2018)
Red Ginger plant is one of the export commodities and has benefits as perfume industry, cosmetics, health, and spices. Currently, the volume of demand for ginger products continues to increase, but the demand has not been met because of low productivity so that the need for intensification and provision of fertilizer. The purpose of this research is to study the effect of urea and cow manure on the growth of red ginger plants and to study the type of urea fertilizer and cow manure that gives maximum effect to growth and the essential oil content of Ginger Red plant. Observed parameter include plant height, leaves numbers, plant wet weight, and essential oil content. The study used Completely Randomized Design (RAL) with 4 treatments and 3 replications. Intended treatments are without fertilizer, with cow manure, with urea fertilizer, and with combination of urea fertilizer and cow manure. Data were analyzed with Analysis of Variance (ANOVA) at 95% significant level. Red ginger plants gave cow manure 150 g / polybags tend to produce plant height, plant wet weight, and higher essential oil content. Key Words : Growth, red ginger, urea fertilizer, cow manure